The effects of white shark presence on the behaviour of Cape fur seals at Geyser Rock, Gansbaai, South Africa - Wcisel, Michelle (Department of Biological Sciences, 2014)
Predators and the risk associated with their presence may affect group composition, group size, movement patterns, and habitat use of prey species. The removal of predators, or their reintroduction following long periods of absence, equally can have profound impacts on their prey, triggering ecological cascades and ultimately shaping the biota of entire landscapes. While such processes are well documented in terrestrial ecosystems, similar results are absent in the marine realm, largely due to logistical difficulty. One exception to this is the study of white shark and seal interactions at coastal island rookeries, where white shark presence is seasonal, and seals exhibit marked behavioural differences between seasons. What is lacking from these studies, however, is how subsurface habitat around the islands, specifically refugia, may influence the behaviour of seals and their interactions with white sharks. I address this challenge by comparing both seal movement patterns and shark-seal interactions at Geyser Rock, Gansbaai with the established seal and shark patterns at Seal Island, False Bay. White sharks aggregate at both islands during the austral winter and seals encounter these aggregations when commuting to and from their respective rookeries to offshore foraging areas. The seascape around Geyser Rock is comparably more featured, including kelp beds and extensive shallow (5-10m depth) reef systems, whereas Seal Island is largely featureless, with neither extensive kelp nor reefs. At Geyser Rock, predations by white sharks were rarely observed (0.1 predations/hour) compared to Seal Island (1.24 predations/hour) and lacked the focused spatiotemporal peak at sunrise to the south of the island. Seals at Geyser Rock did not show a relationship between group formation and season, which was clearly demonstrated at Seal Island. This suggests that seals at Geyser Rock may be less reliant on group formation (safety in numbers) and selfish herd tactics within such groups to reduce predation risk. Rather, seals at Geyser Rock avoided deep open water patches during winter and shifted their movement patterns to and from the island to sectors with greater subsurface habitat heterogeneity. While I was limited in quantifying spatiotemporal patterns of predation risk around Geyser Rock (predation events were rare and widely dispersed), these results strongly suggest that seals actively avoid deep open water and show a preference for high structural complexity sectors during the risky winter months when shark presence is highest. This finding represents a habitat-escape tactic unidentified in previously studied white shark/pinniped systems. Together these results provide empirical support for both the risk-allocation hypothesis and refugia hypotheses within marine predator-prey systems.